How to make the board effective for good practices of corporate governance / Yusniyati Yusri and Mohamad Azmi Nias Ahmad - Yusri, Yusniyati; Nias Ahmad, Mohamad Azmi (2003)
In general, corporate governance is a system on how an enterprise is governed and controlled or the process and structure used to manage business and affairs of a company with accountability. It comprises the internal and external structure of the enterprise, management accountability of its authority and agency through an effective internal control system and legislation, and market control for disclosure of corporate information and transparency of the company's affairs